Centrosomal PKCβII and pericentrin are critical for human prostate cancer growth and angiogenesis - Kim, Jeewon (2008)
Angiogenesis is critical in the progression of prostate cancer. However, the interplay between the proliferation kinetics of tumor endothelial cells (angiogenesis) and tumor cells has not been investigated. Also, protein kinase C (PKC) regulates various aspects of tumor cell growth but its role in prostate cancer has not been investigated in detail. Here, we found that the proliferation rates of endothelial and tumor cells oscillate asynchronously during the growth of human prostate cancer xenografts. Furthermore, our analyses suggest that PKCβII was activated during increased angiogenesis and that PKCβII plays a key role in the proliferation of endothelial cells and tumor cells in human prostate cancer; treatment with a PKCβII-selective inhibitor, βIIV5-3, reduced angiogenesis and tumor cell proliferation. We also find a unique effect of PKCβII inhibition on normalizing pericentrin (a protein regulating cytokinesis), especially in endothelial cells as well as in tumor cells. PKCβII inhibition reduced the level and mislocalization of pericentrin and normalized microtubule organization in the tumor endothelial cells. Although pericentrin has been known to be upregulated in epithelial cells of prostate cancers, its level in tumor endothelium has not been studied in detail. We found that pericentrin is upregulated in human tumor endothelium compared with endothelium adjacent to normal glands in tissues from prostate cancer patients. Our results suggest that a PKCβII inhibitor such as βIIV5-3 may be used to reduce prostate cancer growth by targeting both angiogenesis and tumor cell growth.